Analisa dan Perancangan Sistem Aplikasi Digitalisasi Arsip dengan Metode Rapid Aplication Development (RAD) - Yuli Hermawan (Jurnal Riset Informatika dan Inovasi, 2023)
In today's digital era, many organizations and companies face challenges in managing and accessing their records efficiently. Manual processes involving physical documents can be slow, inefficient and prone to human error. Therefore there is a need for a solution that can assist organizations in optimizing and optimizing the archive process. Currently information and communication technology has become an important component for the operations of companies, institutions and organizations. With the development of information and communication technology, the form of information recording has also shifted from conventional forms such as paper to more modern electronic forms, either in part or in whole. Digitizing paper archives onto new media needs to be done as a part of archive preservation. The application of digitizing archives has benefits including avoiding damage to information contained in physical archives due to organisms, human error or loss due to natural disasters. By digitizing archives, archival information on obsolete paper media can be preserved and the information contained therein can be reused. Analysis and design of archive digitization systems does not only focus on scanning archives, but also on archive storage, retrieval facilities when archives are needed and access rights to archives that have been transferred media and also archive shrinkage of archives that have expired. The analysis and design of this archive digitization system uses the Rapid Application Development method. With the stages of determining application requirements, making application prototypes, the development process and collecting feedback as the stage of improving application systems, implementing and finalizing applications. Keywords: archive; paper; digitization; preservation; sustainable